Independent Predictive Factors of Hospitalization in a North-West Burn Center of Iran; an Epidemiologic Study - Shams Vahdati, Samad; Hazhir Karzar, Bita; Momen, Negar (Archives of Academic Emergency Medicine, 2018)
Introduction:Â A high grade burn is one of the most devastating injuries with several medical, social, economic, and psychological effects. These injuries are the most common cause of accidental deaths after traffic injuries in both the developed and developing countries. Therefore this research was aimed to determine demographic characteristics of patients with burn injury admitted to the emergency department and identify predictive factors of hospitalization.Â Methods:Â This is a cross sectional descriptive study, which is done in 20 March up to 20 September 2011 in emergency department of Sina Hospital, Tabriz, Iran. Patientsâ€™ information including demographic characteristic, cause of burn, place of accident, anatomical areas burned, grading and percent of burning and disposition were gathered and analyzed using SPSS version 18.0 statistical software. Stepwise multivariate regression analysis was used for recognition of independent predictive factors of hospitalization in burned patients.Â Results:Â One hundred and sixty patients were enrolled (54.4% female). The average age of those was 20.47Â±13.5 years. The prevalence of burn was significantly higher in ages under 20 years (p<0.001). Lower limb (37.5%), head and neck (21.25%) and upper limb (17.5%) were three frequent site of burn. The most common cause of burns was boiling water scalding (34.4%). Home related burn was significantly higher than other place (p<0.001). The most frequent percent of burn was <5% (46.25%). Finally 50 (31.25%) cases hospitalized. Univariate analysis demonstrated that age under 20 years old (p=0.02) female gender (p=0.02), burning site (p=0.002), cause (p=0.005), place (p<0.001), grade (p<0.001), and percent (p<0.001) was related to disposition of patients. Stepwise multiple logistic regression showed female gender (OR=3.52; 95% CI: 1.57-7.88; p=0.002), work related burning (OR=1.78; 95% CI: 1.26-2.52; p=0.001), and burning over 5 percent (OR=2.15; 95% CI: 1.35-3.41; p=0.001) as independent predictive factors of hospitalization.Â Conclusion:Â The results of present study showed that burns injury are most frequent in age under 20 year old, lower limbs, with boiling water, and at home. Also the most frequent type and percentage of burned area were second degree and <5% of total body surface area, respectively. Among age under 20 years old, female gender, burning site, cause, place, grade, and percent only female gender, work related burning, and burning over 5% were detected as independent predictive factors of hospitalization.